Peran panitera dalam praktek sistem peradilan pidana Indonesia - Puji Setiawan; Lilik Mulyadi; Eko Nurharyanto (Kajian Hasil Penelitian Hukum, 2019)
This thesis is entitled "The Role of Clerks in the Practice of the Indonesian Criminal Justice System". The thesis with the title aims to find out and analyze the existence of the Registrar in the practice of the Indonesian criminal justice system and to find out the role of the ideal clerk in the practice of the Indonesian criminal justice system. This research is a normative study with a statutory approach. Source of data in the form of secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data collection method uses library research (interview) and interviewees. Primary legal materials and secondary legal materials were analyzed using legal analysis methods. The purpose of the above method can be interpreted that the research method is a knowledge to explore the truth of a methodological systematically in accordance with applicable research guidelines in scientific papers. Increasing the credibility and transparency of the judiciary is a goal of the Supreme Court in an effort to realize a judiciary that can provide maximum public service. A Registrar and officials under him are fully responsible for the administrative duties carried out by the commander of the case until the case is legally binding on the Chief Justice and always under the command of the Chief Justice. Based on this difference in duties and responsibilities between a Judge and the duties of a Court Clerk. In the criminal justice process a lot of clerks' tasks especially with the advancement of information technology as it is now many applications launched by the Supreme Court of the Republic of Indonesia. from E-Court, E-Litigation, Case Search Information System (SIPP) there are some Courts that have used the Audio Text Recording Application or better known as ATR. The role of the court clerk is not only as a courtesan preacher but has a very important role in the practice of the criminal justice system.